Empathy and bystander helping behavior in cyberbullying among adolescents: the mediating role of internet moral judgment and the moderating role of internet self-efficacy - Hu, Yang; Zhang, Tian; Shi, Hui-fen; Fan, Cui-ying (Frontiers in Psychology, 2023)
Cyberbullying poses a significant challenge among adolescents. If bystanders stand up and help victims, their helping behavior they may be able to reduce the frequency and negative impact of cyberbullying. This study investigates the influence association of empathy, internet moral judgment, and internet self-efficacy on with bystander helping behavior among adolescents witnessing cyberbullying incidents. By surveying 919 Chinese adolescents using a questionnaire, we constructed a moderated mediation model to examine the relationship between empathy and bystander helping behavior in cyberbullying and assessed the mediating role of internet moral judgment and the moderating role of internet self-efficacy. Our findings revealed a significant positive correlation between empathy and bystander helping behavior in cyberbullying. Internet moral judgment mediated the relationship between empathy and helping behavior, whereasile internet self-efficacy moderated the latter half of the mediation pathway. Specifically, the influence association betweenof internet moral judgment on and helping behavior was greater stronger for bystanders with higher levels of internet self-efficacy compared to with those that with have lower levels. These results further deepen and enrich our understanding of the mechanisms influencing involved in bystander helping behavior in cyberbullying, thus providing a basis for future interventions to encourage more helping actions from bystanders during cyberbullying incidents.